2021
DOI: 10.1038/s41529-021-00206-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologically influenced corrosion inhibition of carbon steel via biomineralization induced by Shewanella putrefaciens

Abstract: Microbiologically influenced corrosion inhibition (MICI) of Q235 carbon steel by biomineralization was investigated via a combination of surface analysis, electrochemistry, and scanning electrochemical microscopy (SECM). The results showed that Shewanella putrefaciens used the cell walls as the nucleation sites to induce the formation of a protective biomineralized layers which contained calcite and extracellular polymeric substances on the steel surface. The potentiodynamic polarization results demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…The negatively charged functional groups in EPS, such as -NH 2 , -COOH, -C-O-C, and -OH, first adsorb positively charged metal ions to form complexes. Then, EPS interact with metal ions by oxidation and precipitation to form biomineralized layers on the metal surface, which can protect metals from corrosive environments such as seawater [ 56 , 128 , 129 ]. The EPS control the kinetic pathway of CaCO 3 , biomineralizing nucleation and CaCO 3 crystal growth.…”
Section: Eps and Biocorrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negatively charged functional groups in EPS, such as -NH 2 , -COOH, -C-O-C, and -OH, first adsorb positively charged metal ions to form complexes. Then, EPS interact with metal ions by oxidation and precipitation to form biomineralized layers on the metal surface, which can protect metals from corrosive environments such as seawater [ 56 , 128 , 129 ]. The EPS control the kinetic pathway of CaCO 3 , biomineralizing nucleation and CaCO 3 crystal growth.…”
Section: Eps and Biocorrosionmentioning
confidence: 99%
“…Recently, it was shown that a marine isolate of P. stutzeri can promote the formation of a protective biomineralization film, which had a good inhibition effect against steel corrosion [ 134 ]. S. putrefaciens could use cell walls as the nucleation sites to induce the formation of a protective biomineralized layer, which contained calcite and EPS on the steel surface [ 129 ].…”
Section: Eps and Biocorrosionmentioning
confidence: 99%
“…Copyright (2015) John Wiley and Sons. (b, c) SECM images of a coating scratch during the S. putrefaciens ‐induced microbial self‐healing process before and after 7 days in the S. putrefaciens ‐inoculated medium [13c] . Reproduced with permission from Ref.…”
Section: Applications Of Secm In Biofilm Studiesmentioning
confidence: 99%
“…This microbiological influenced corrosion inhibition (MICI) is considered a reliable and environmentally friendly strategy for corrosion protection. To investigate the influence of S. putrefaciens on the microbially influenced corrosion inhibition process, SECM was applied to probe the oxygen concentration close to the scratched region of Q235 carbon steel [13c] . As shown in Figure 4b, the S. putrefaciens layer showed anti‐abrasive and self‐healing properties, and the corrosion of the steel was finally inhibited by the biomineralized layers induced by S. putrefaciens (Figure 4c).…”
Section: Applications Of Secm In Biofilm Studiesmentioning
confidence: 99%
“…The effects of microbes on corrosion are two-fold [34]. Besides the corrosion-accelerating effect of bacteria, microbes can directly or indirectly mitigate corrosion via processes known as microbiologically influenced corrosion inhibition (MICI) [35,36]. MICI can be achieved by microbial respiration consumption of corrosive substances, formation of mineralized layers, formation of EPS protective layer, competitive microbial corrosion inhibition or microbial secretion of corrosion inhibitors [37].…”
Section: Introductionmentioning
confidence: 99%